A Numerical Analysis of the Stress-strain Behavior of Anchorage Elements and Steel Liner of a Prestressed Concrete Containment Wall. (November 2017) - Bílý, Petr; Kohoutková, Alena
Abstract: The paper presents a numerical analysis of the stress-strain behavior of the steel liner of a prestressed concrete containment wall and the anchorage elements between the liner and the wall. Models of a block segment of the wall were created and loaded by prestress, operation temperature, creep and shrinkage, loss of coolant accident (LOCA) temperature and LOCA pressure. The purpose of the block models was to observe the stress-strain behavior of the steel liner plate in the course of service life of the structure and to obtain boundary conditions for the detailed models of anchorage elements connecting the liner to the concrete wall. There were two different types of anchorage studied – headed studs and L-profiles. The detailed models of anchorage elements were loaded by displacements calculated in the block models and exploited for the determination of extreme stresses in the steel liner and widths of cracks in the concrete wall. The importance of initial geometry imperfections of the steel liner plate was appraised as well. According to the results, there is no risk of buckling of the liner or failure of the liner and anchorage elements during operation conditions and LOCA. There is also no substantial difference between the stress-strain behavior of the liners connected by headed studs or by L-profiles. However, the initial imperfections of the liner plate were found to be very important for the distribution of stresses in the liner and crack pattern in concrete.